Use Tableau desktop to show multiple measures at once - Allchin, Carl (O'Reilly Media, Inc., 2024)
Tableau is one of today's most powerful business intelligence analytics and data visualization tools. It empowers people across the organization to see and understand data for better business decision-making. These Shortcuts will provide you with simple tips and tricks for creating charts, dashboards, and stories that turn data into actionable insights.
Keywords: Tableau (Computer file); Information visualization -- Computer programs; Visual analytics -- Data processing; Visualisation de l'information; Logiciels; Analyse visuelle; Informatique